2012
DOI: 10.1155/2012/786417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mammary Cancer in 7,12-Dimethylbenz(a)anthracene-Induced Wister Rats by Asymmetrical Temperature Distribution Analysis Using Thermography: A Comparison with Serum CEA Levels and Histopathology

Abstract: Animal surface temperature profile captured using infrared camera is helpful for the assessment of physiological responses associated with the regulation of body temperature. Diagnosing breast cancer in early stage itself has a greater effect on the prognosis. In this work, asymmetrical temperature distribution analysis of chemical carcinogen 7,12-dimethyl benz(a)anthracene-induced in the lower right flank region of Wistar rats (n = 6) was carried out to test the potential of thermography in diagnosing mammary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In the context of the tumorigenic potential of DMBA, it was reported that DMBA induced mammary cancer in Wistar rats in a study that evaluated the diagnostic value of thermography in comparison to histopathology as the gold standard. 16 This mammary carcinogenic effect of DMBA has also been reported by another group. 17 Likewise, mammary cancer was induced in FVB mice after administration of six doses of DMBA, wherein a number of genetic aberrations and protein post-translational modifications occurred, including overexpression of c-myc, aryl hydrocarbon receptor cyclin-D1, and hyperphosphorylation of retinoblastoma.…”
Section: Discussionsupporting
confidence: 74%
“…In the context of the tumorigenic potential of DMBA, it was reported that DMBA induced mammary cancer in Wistar rats in a study that evaluated the diagnostic value of thermography in comparison to histopathology as the gold standard. 16 This mammary carcinogenic effect of DMBA has also been reported by another group. 17 Likewise, mammary cancer was induced in FVB mice after administration of six doses of DMBA, wherein a number of genetic aberrations and protein post-translational modifications occurred, including overexpression of c-myc, aryl hydrocarbon receptor cyclin-D1, and hyperphosphorylation of retinoblastoma.…”
Section: Discussionsupporting
confidence: 74%
“…, Heffelfinger et al and Al‐Ghananeem et al as a reliable method which could be reconfirmed by histopathological evaluation. Although some adjunct methods like thermography are suggested , palpation and determination of tumor size are still the mainstays for detection of tumor formation.…”
Section: Methodsmentioning
confidence: 99%
“…To induce breast cancer in rats, a single dosage of 25 mg of 7,12‐DMBA dissolved in 1 mL of soy oil was administered subcutaneously into the 2nd set of mammary glands 39–42 . The chemical carcinogen was administered when the rats were aged between 60 and 65 days 43–46 .…”
Section: Methodsmentioning
confidence: 99%
“…To induce breast cancer in rats, a single dosage of 25 mg of 7,12-DMBA dissolved in 1 mL of soy oil was administered subcutaneously into the 2nd set of mammary glands. [39][40][41][42] The chemical carcinogen was administered when the rats were aged between 60 and 65 days. [43][44][45][46] The tumor was first detected by touch and its size was subsequently measured and monitored regularly.…”
Section: Animals and Experimental Groupsmentioning
confidence: 99%